STUDI KOMPARATIF SYARAT-SYARAT PERKAWINAN BERDASARKAN UNDANG-UNDANG PERKAWINAN NOMOR 16 TAHUN 2019 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 1 TAHUN 1974 DAN KOMPILASI HUKUM ISLAM - LARASATI NIM. A1011161010 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac Fulfilling the requirements to say a marriage is valid, by using the provisions of marriage law and religious law of the parties, contains aspects of legal protection that regulate and protect the parties. Law No. 1 of 1974 actually recognizes and regulates the religious law of the parties, which means that non-fulfillment of the formal requirements, namely the requirements for marriage procedures to fulfill their religious law, is also a violation of the provisions of marriage law based on Law No. 1 of 1974. In this law, the minimum age for marriage for women is equated with the minimum age for marriage for men, which is 19 (nineteen) years (Article 7 paragraph (1) of Law Number 16 of 2019 concerning marriage). This age limit is considered to be physically and mentally mature to be able to enter into a marriage in order to realize the purpose of marriage properly so that it does not end in divorce and produce healthy and quality offspring.So what is the main problem in this writing is: